2007
DOI: 10.1590/s1414-32832007000100003
|View full text |Cite
|
Sign up to set email alerts
|

A construção do saber em Odontologia: a produção científica de três periódicos brasileiros de 1990 a 2004

Abstract: Este estudo focaliza uma análise das temáticas abordadas por três revistas odontológicas brasileiras, durante o período de 1990 a 2004. Partimos do pressuposto de que estas têm um papel importante na formação profissional, pois são meios dinâmicos de divulgação do saber e, desta forma, podem influenciar e nortear pensamentos, reflexões e atitudes, moldando o fazer odontológico. A análise quantitativa do material empírico, totalizando 2.806 artigos estudados, revela a diversidade de temáticas e assuntos das pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 10 publications
0
3
0
6
Order By: Relevance
“…These results are in agreement with another study analyzing the different fields of dentistry research in three Brazilian scientific journals between 1990 and 2004; this previous study found that the greatest number of published papers focused on restorative dentistry/dental materials and public health. 5 Narvai states that the increase in publications on public health is not sufficient to classify this field as one of the most productive in dental research, but a growing interest in this field seems to be a current trend. 8 There are several interesting findings in the results for 2009.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in agreement with another study analyzing the different fields of dentistry research in three Brazilian scientific journals between 1990 and 2004; this previous study found that the greatest number of published papers focused on restorative dentistry/dental materials and public health. 5 Narvai states that the increase in publications on public health is not sufficient to classify this field as one of the most productive in dental research, but a growing interest in this field seems to be a current trend. 8 There are several interesting findings in the results for 2009.…”
Section: Discussionmentioning
confidence: 99%
“…All abstracts (n = 2648) were classified based on registration category and field of knowledge using the method proposed by Amorim et al 5 This classification scheme discriminates topics by dividing fields of knowledge into 25 categories based on the most frequently addressed topics in Brazilian dental literature over the past 15 years. This method was adopted in the present investigation to facilitate comparisons between the current study and previous studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No mundo científico moderno, em que observamos um aumento no número de pesquisas, as revistas científicas desempenham um papel importante, pois são maneiras dinâmicas de divulgar o conhecimento produzido 5 .…”
Section: Discussionunclassified
“…Como bem registrado por Amorim et al (2007) 14 , dentre as três principais revistas odontológicas nacionais, no período 1993-2004, os artigos relacionados à política/economia ou temas assemelhados compuseram 0,78% do total dos artigos (2.086). Quando se desagregou a frequência da categoria pelas revistas, em duas delas, os artigos sobre política, dentre 25 colocações, ocupavam a última posição.…”
Section: Introductionunclassified